Simbolisme Integrasi Islam dan Budaya Jawa dalam Tradisi Nyadran: Studi di Desa Ngayung Lamongan - Hartianti, Ayu Ning Tyas; Halim, Abdul (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2025)
Tradition is a form of culture that is passed down from generation to generation and serves as a marker of social identity. In Java, the acculturation of local culture with Islam since the Walisongo era gave rise to traditions rich in symbolism, one of which is Nyadran. This study aims to analyze the symbolic meanings within the Nyadran tradition in Ngayung Village, Lamongan, and to explain how these symbols represent the integration of Islam and Javanese culture. The research employed a qualitative method with cultural and Islamic anthropological approaches. Data were collected through observation, in-depth interviews with religious leaders, community elders, and local residents, as well as documentation, with validity tested through source triangulation. The findings reveal that Nyadran is divided into two types: the small Nyadran (held before Ramadan) and the large Nyadran (after the second harvest). The main symbols include buffalo slaughter as a representation of cleansing oneself from laziness and ignorance, sticky rice as a symbol of togetherness and gratitude, as well as prayers, tahlil, and religious gatherings reflecting Islamic spirituality. This tradition functions as a medium of social education, reinforcement of solidarity, and maintenance of communal harmony. Thus, Nyadran in Ngayung Village is not only of historical and religious value but also serves as an instrument of integration between Islam and Javanese culture while strengthening the community’s religious and cultural identity.